Comparison of Duffy Blood Group System Genotype in Kurdish Patients with Beta-Thalassemia Major in Kermanshah City: A Case-Control Study - Ali Maleki; Marivan Noori; Rezvan Zomorodi; Fakhredin Saba (Tehran University of Medical Sciences, 2022)
Background and Ami: Identifying the genotype of blood groups in different communities will give the decision makers of the health system to take the necessary measures to prevent and identify the possible side effects of blood transfusion, including the production of alloantibodies. Duffy blood group has increased the possibility of alloantibody production in beta-thalassemia major patients who regularly need blood transfusion due to different types of genotype with different prevalence. However, no study has been conducted regarding the frequency of Duffy blood group distribution in beta-thalassemia Kurd patients dependent on blood transfusion. Materials and Methods: This case-control study was conducted on 100 patients with beta thalassemia major, as case group and 50 healthy individuals, as control group, in Bostan Clinic, Kermanshah University of Medical Sciences. After collecting peripheral blood samples from people participating in the study, DNA was extracted from peripheral blood mononuclear cells. Then, using PCR-RFLP and electrophoresis, Duffy genotypes including FYA/A, FYB/B and FYA/B were identified. Results: The results of Chi-square test showed that in the patient group, there is no statistically significant difference between the two genders in terms of the frequency of distribution of Duffy genotypes (P=0.588). On the other hand, in the healthy group too, there was no statistically significant difference between the two sexes in terms of the frequency of distribution of Duffy genotypes (P=0.707). According to nominal regression results, although the distribution ratio rate (95% confidence interval) of FYA/FYA and FYB/FYB genotypes as compared to FYA/FYB genotype (reference category) in the patient group as compared to healthy people was 2.42 (0.7 to 8.34) and 0.76 (0.36 to 1.64) respectively, but there was no statistically significant difference between the case and control groups in terms of the distribution frequency of these genotypes (P<0.05). Conclusion: The frequency distribution of Duffy genotypes in beta-thalassemia major patients is similar to that of healthy people, and there is no relationship between the distribution of Duffy genotypes and beta-thalassemia disease. FYB genotype has the highest frequency in both case and control groups